The Potential of Iodine Lactoglycerol as an Alternative Fungal Stain in the Laboratory - Lilis Puspa Friliansari; Erick Khristian; Sofie Agustina Hermawanti (Biomedika, 2020)
Fungi are eukaryotic and opportunistic organisms that can cause damage and disease. Fungi can be identified by direct staining. The composition of the dyes used in fungi staining are toxic, mutagenic and harmful to laboratory personnel and the environment. Consequently, it is necessary to consider use fungi dye continuously, so its need alternative safety dyes to identify fungi in the laboratory. This research aims to determine the potential of iodine lactoglycerol with different concentrations (1.25%, 2.5%, and 5%) as an alternative dye for fungi in the laboratory. The research method used experimental design. The samples originate from moldy bread and made 27 of microscopic slides. The microscopic slides were observed with objective 40x magnification. The parameters assessed in this study were the structure and morphology of fungi including hyphae, conidiophores, vesicles, sterigmata and conidiospores and color intensity using the image analysis of ImageJ. The results showed that various concentrations of iodine lactoglycerol can staining the structure and morphology of the fungi properly and clearly. The value of color intensity of each concentration measured has a different average. The highest average value of color intensity concentration was 5% and the lowest was 1.25%. However, the result of ANOVA test showed a significance of 0.380 (P> 0.05), which means that is no difference significantly from three of various concentrations. The result showed that the difference concentration of iodine lactoglycerol does not affect the color intensity. The conclusion of this study was iodine lactoglycerol solution can be used as an alternative dye or Lactophenol-cotton Blue (LPCB) substitute for fungi identification. It is recommendation for further research be carried out regarding the decrease in the concentration of alternative color solutions below 1.25%, the incubation time for the preparation of the preparations, and the color stability of the prepared mushroom preparations.